Association of electroencephalogram epileptiform discharges during cardiac surgery with postoperative delirium: An observational study - Li, Na; Liu, Xing; Gao, Yuhua; Yin, Lingzi; Zhao, Wanli; Ma, Rongxing; Ni, Xinli (Frontiers in Surgery, 2022)
Background Delirium is a frequent and serious complication following cardiac surgery involving cardiopulmonary bypass (CPB). Electroencephalography reflects the electrical activity of the cerebral cortex. The impact of electroencephalographic epileptiform discharges during cardiac surgery on postoperative delirium remains unclear. This study was designed to investigate the relationship between intraoperative epileptiform discharges and postoperative delirium in patients undergoing cardiac surgery. Methods A total of 76 patients who underwent cardiac surgery under CPB were included. The baseline cognitive status was measured before surgery. Electroencephalograms were monitored continuously from entry into the operating room to the end of surgery. The presence of delirium was assessed through the Confusion Assessment Method or the Confusion Assessment Method for the Intensive Care Unit on the first 3 days after surgery. Univariate and multivariate logistic regression analyses were performed to evaluate the association between epileptiform discharges and delirium. Results Delirium occurred in 31% of patients and epileptiform discharges were present in 26% of patients in the study. Patients with delirium had a higher incidence of epileptiform discharges (52.63% vs. 13.95%, P < 0.001) and longer durations of anesthesia and CPB (P = 0.023 and P = 0.015, respectively). In addition, patients with delirium had a longer length of hospital stay and a higher incidence of postoperative complications. Multivariate logistic regression analysis showed that age and epileptiform discharges were significantly associated with the incidence of postoperative delirium [odds ratio, 4.75 (1.26–17.92), P = 0.022; 5.00 (1.34–18.74), P = 0.017, respectively]. Conclusions Postoperative delirium is significantly related to the occurrence of epileptiform discharges during cardiac surgery.